Students' Perception: The Use of Story-Mapping Strategy in Teaching Narrative Text at SMA Negeri 1 Kedungreja - Utami, Sri (IJET (Indonesian Journal of English Teaching), 2025)
Teaching strategies play a crucial role for English teachers and students in achieving the expected learning objectives, especially when teaching narrative texts at Senior High School. Story-mapping strategy is a practical approach to apply in teaching narrative texts because it has numerous influences on improving students' learning. Many previous studies have discussed the effectiveness of the story-mapping strategy. However, it is not explained in depth how the teacher uses the story-mapping strategy in teaching narrative texts, nor are students' perceptions of the use of the story-mapping strategy in teaching narrative texts discussed. This research aims to describe teachers' approaches to using the story-mapping strategy and to investigate students' perceptions of that strategy. To answer that, the researchers conducted interviews, observations, and distributed questionnaires. The method is a qualitative descriptive method. Results show that there are five steps used by the teacher when employing the story-mapping strategy in teaching narrative texts—step 1. The teacher teaches the material using charts—step 2. The teacher introduces the concept of the story-mapping strategy—step 3. The teacher introduces the parts of the story-mapping graphics—step 4. The teacher asks students to reread the narrative story (step 5). The teacher asks students to complete the story-mapping graphics. Regarding the students' perceptions of the use of the story-mapping strategy in teaching narrative texts at SMA Negeri 1 Kedungreja, the students perceive several advantages in using this strategy, categorised into three aspects: students' feelings, teacher performance, and the effect of the story-mapping strategy. Related to aspects of students' feelings, the story-mapping strategy makes the students happy, comfortable, and motivated to learn. Concerning the teacher’s performance, students can learn in a fun and relaxed atmosphere. Lastly, regarding the effect of using the story-mapping strategy, students can improve their ability to understand the material and solve their learning problems.